Health literacy among patients with poor understanding of prescription drug label instructions in Saudi Arabia - Ahmed AbuAlreesh; Khalid A. Alburikan (Elsevier, 2019)
Introduction: This study conducted to assess the health literacy level among patients who have poor understanding of the medications' labels in Saudi Arabia. Methods: This multi-center cross-sectional study was conducted on two phases. In the 1st phase, 511 patients waiting for their medications in the outpatient pharmacies of four major hospitals in Saudi Arabia were interviewed to assess their understanding ability of the labels of five of the commonly prescribed medications. Those participants who misunderstood the medications' labels were enrolled in the 2nd phase of the study to assess their health literacy level. The validate Arabic Single Item Literacy Screener (SILS) was used to assess the health literacy level. Analysis: The sample characteristics were described by mean and percentage. Both Chi-square test and logistic regression model were used to figure out the association between health literacy with the main affecting factors. Results: Almost 38.6% (n = 197) of the participants in phase-1 misunderstood the medications' labels. Nearly, 11.2% (n = 22) of them had low health literacy level. Participants who had low education level and low socioeconomic status were more likely to have low health literacy [adjusted odds ratio (AOR) = 2.94; 95% confidence interval (95%CI) (1.03-8.404); P-value = 0.044], [AOR = 5.28; 95%CI (1.118-24.943); P-value = 0.036], respectively. Conclusion: Low health literacy was associated with low education level and low socioeconomic status of the patients. Keywords: Health literacy, Medication label, Label understanding, Misunderstanding, Education level